PERENCANAAN PERKUATAN TEBING DI BANTARAN SUNGAI METRO KECAMATAN SUKUN KELURAHAN KARANGBESUKI KABUPATEN MALANG - Ximenes, Leonardo Da Cruz; Sulistyani, Kiki Frida; Suhudi, Suhudi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Some communities in Malang still much settled in areas close to the river banks or cliffs. In this case to note there are many who rely on the land retaining wall as a cantilever aides foundatin on peoples homes. Retaining walls can be said to be safe if the retaining wall has been considered the safety factor, both against the dangers of the shift, the danger of overthrow, reduced bearing capacity and fracture. Planning retaining wall is located in a residential of Graha Indah Santosa on a Karangbesuki metro river bank Karangbesuki metro Village, Sukun District, Malang. The planned retaining wall is the type of gravity. In order to this building function properly, then the stability of the building should also be good. Therefore, the author tries to analyze the stability of the retaining wall to the danger of rolling and sliding toward normal water level conditions without the earthquake, with earthquake and toward flood water level conditions without the earthquake, with earthquakes. Calculation using the formula Rankine. As a result, Sfsliding 1,82> 1.5 and 1.65> 1.2 SFshear 1.9> 1.5 and 1.57> 1.2 (for normal conditions without and with earthquake) and SFsliding 1.9> 1,5 and 1.8> 1.2, SFshear 1.65> 1.5 and 1.35> 1.2 (for flood conditions without and with earthquake) turns secure. This study is also included with the calculation of the total budget plan is Rp. 675.980,002 Key words : River metro, retaining wall, Stability